Terrestrial formation of calcium sulfate and carbonate assemblages in Atacama CO chondrites: Implications for Martian evaporitic environments - Gabriel A. Pinto; Vinciane Debaille; Jolantha Eschrig; Alexandre Corgne; Kevin Soto; Thierry Leduc; Sophie Decree; Steven Goderis (Icarus, 2026)

Impact of minerals on the microbial species diversity and metabolite dynamics during spontaneous backslopped wheat sourdough productions - Yohanes Raditya Wardhana; Víctor González-Alonso; Inés Pradal; Steven Goderis; Frédéric Leroy; Luc De Vuyst (International Journal of Food Microbiology, 2026)

Absence of Fe isotope fractionation in Cretaceous-Paleogene impact spherules: insights into the thermodynamic processes in the Chicxulub impact plume - Ségolène Rabin; Steven Goderis; Lisa Krämer-Ruggiu; Pim Kaskes; Jan Smit; Kasper Hobin; Frank Vanhaecke; Philippe Claeys (Earth and Planetary Science Letters, 2026)

Clumped isotope reordering kinetics in rudist fossils: Impact of burial history and paleoclimatic implications - Barbora Křížová; Niels J. de Winter; Martin Ziegler; Alberto Riva; Philippe Claeys; Steven Goderis; Deborah Arbulla; Gianluca Frijia (Geochimica et Cosmochimica Acta, 2025)

Diversity among fossil micrometeorites in the late Devonian - Lisa Krämer Ruggiu; Johan Villeneuve; Anne-Christine Da Silva; Vinciane Debaille; Sophie Decrée; Lutz Hecht; Felix E.D. Kaufmann; Steven Goderis (Geochimica et Cosmochimica Acta, 2025)

Structural inheritance and hydrothermal alteration impact on fluid circulation in a clay-rich shear zone - Benjamin Avakian; Béatrice A. Ledésert; Ghislain Trullenque; Ronan L. Hébert; Johanne Klee; Sébastien Potel; Titouan Miloikovitch; Steven Goderis; Philippe Claeys (Journal of Structural Geology, 2025)

Microstructures and sclerochronology of the Lithiotis Facies bivalves (Lower Jurassic): Paleobiological and paleoclimatic significance and their resilience to the early Toarcian extinction - Renato Posenato; Gaia Crippa; Niels J. de Winter; Philippe Claeys; Steven Goderis; Gianluca Frijia; Valentina Brombin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Chrome-rich spinels in micrometeorites from modern Antarctic sedimentary deposits - Flore Van Maldeghem; Ryoga Maeda; Bastien Soens; Martin D. Suttle; Lisa Krämer Ruggiu; Carole Cordier; Akira Yamaguchi; Birger Schmitz; Philippe Claeys; Luigi Folco; Steven Goderis (Earth and Planetary Science Letters, 2024)

Identification of Earth's late accretion by large impactors through mass independent Cr isotopes - Yogita Kadlag; Aryavart Anand; Mario Fischer-Gödde; Klaus Mezger; Kristoffer Szilas; Steven Goderis; Ingo Leya (Icarus, 2024)

A new insight of the MIS 3 Dansgaard-Oeschger climate oscillations in western Europe from the study of a Belgium isotopically equilibrated speleothem - Marion Peral; Marta Marchegiano; Sophie Verheyden; Steven Goderis; Tom Van Helden; Frank Vanhaecke; Thibaut Van Acker; Xue Jia; Hai Cheng; Jens Fiebig; Tiffanie Fourcade; Christophe Snoeck; et al. (Quaternary Science Reviews, 2024)

Moderately volatile elemental and isotopic variations in variably shocked equilibrated ordinary chondrites from Antarctica - Jérôme Roland; Vinciane Debaille; Hamed Pourkhorsandi; Steven Goderis (Icarus, 2024)

The identification of airbursts in the past: Insights from the BIT-58 layer - Matthias van Ginneken; Ralph P. Harvey; Steven Goderis; Natalia Artemieva; Mark Boslough; Ryoga Maeda; Jérôme Gattacceca; Luigi Folco; Akira Yamaguchi; Corinne Sonzogni; Penelope Wozniakiewicz (Earth and Planetary Science Letters, 2024)

Questioning the role of methane in the wake of a snowball Earth: Insights from isotopically anomalous cap dolostone cements with a complex diagenetic history - Huan Cui; Kouki Kitajima; Ian J. Orland; Jean-Marc Baele; Adam Denny; Michael J. Spicuzza; John H. Fournelle; Steven Goderis; Niels J. de Winter; John W. Valley (Geochimica et Cosmochimica Acta, 2024)

Temperature and hydrological variations during the late-glacial in the Central Mediterranean: Application of the novel ostracod-clumped isotope thermometer - Marta Marchegiano; Marion Peral; Rebecca Doyle; Antonio García-Alix; Alexander Francke; Christophe Snoeck; Steven Goderis; Philippe Claeys (Earth and Planetary Science Letters, 2024)

Geochemical characterization of scoriaceous and unmelted micrometeorites from the Sør Rondane Mountains, East Antarctica: Links to chondritic parent bodies and the effects of alteration - Flore Van Maldeghem; Matthias van Ginneken; Bastien Soens; Felix Kaufmann; Seppe Lampe; Lisa Krämer Ruggiu; Lutz Hecht; Philippe Claeys; Steven Goderis (Geochimica et Cosmochimica Acta, 2023)

A comprehensive evaluation of sulfur isotopic analysis (δ34S and δ33S) using multi-collector ICP-MS with characterization of reference materials of geological and biological origin - Katerina Rodiouchkina; Ilia Rodushkin; Steven Goderis; Frank Vanhaecke (Analytica Chimica Acta, 2023)

The Chicxulub impact structure reveals the first in-situ Jurassic magmatic intrusions of the Yucatán Peninsula, Mexico - Sietze J. de Graaff; Catherine H. Ross; Jean-Guillaume Feignon; Pim Kaskes; Sean P.S. Gulick; Steven Goderis; Thomas Déhais; Vinciane Debaille; Ludovic Ferrière; Christian Koeberl; Nadine Mattielli; Daniel F. Stockli; et al. (Lithos, 2023)

Biodegradable, metal-chelating compounds as alternatives to EDTA for cultivation of marine microalgae - Justine Sauvage; Gary H. Wikfors; Koen Sabbe; Nancy Nevejan; Steven Goderis; Philippe Claeys; Xiaoxu Li; Alyssa Joyce (Journal of Applied Phycology, 2021)
Iron (Fe) is an essential nutrient for microalgal metabolism. The low solubility of Fe in oxic aquatic environments can be a growth-limiting factor for phytoplankton. Synthetic chelating agents, such as ethylenediaminetetraacetic acid (EDTA), are used widely to maintain Fe in solution for microalgal cultivation. The non-biodegradable nature of EDTA, combined with sub-optimal bioavailability of Fe-EDTA complexes to microalgae, indicates opportunity to improve microalgal cultivation practices that amplify production efficiency and environmental compatibility. In the present study, the effects of four organic chelating ligands known to form readily bioavailable organic complexes with Fe in natural aquatic environments were investigated in relation to growth and biochemical composition of two marine microalgae grown as live feeds in shellfish hatcheries ( Chaetoceros calcitrans and Tisochrysis lutea ). Three saccharides, alginic acid (ALG), glucuronic acid (GLU), and dextran (DEX), as well as the siderophore desferrioxamine B (DFB), were compared to EDTA. Organic ligands characterized by weaker binding capacity for cationic metals (i.e., ALG, GLU, DEX) significantly improved microalgal growth and yields in laboratory-scale static batch cultures or bubbled photobioreactors. Maximal microalgal growth enhancement relative to the control (e.g., EDTA) was recorded for GLU, followed by ALG, with 20–35% increase in specific growth rate in the early stages of culture development of C. calcitrans and T. lutea . Substitution of EDTA with GLU resulted in a 27% increase in cellular omega 3-polyunsaturetd fatty acid content of C. calcitrans and doubled final cell yields. Enhanced microalgal culture performance is likely associated with increased intracellular Fe uptake efficiency combined with heterotrophic growth stimulated by the organic ligands. Based upon these results, we propose that replacement of EDTA with one of these organic metal-chelating ligands is an effective and easily implementable strategy to enhance the environmental compatibility of microalgal cultivation practices while also maximizing algal growth and enhancing the nutritional quality of marine microalgal species commonly cultured for live-feed applications in aquaculture.

Late-Holocene sedimentation and sodium carbonate deposition in hypersaline, alkaline Nasikie Engida, southern Kenya Rift Valley - Gijs De Cort; Florias Mees; Robin W. Renaut; Matthias Sinnesael; Thijs Van der Meeren; Steven Goderis; Edward Keppens; Anthony Mbuthia; Dirk Verschuren (Journal of Paleolimnology, 2019)